Optimasi Multi-Objektif Proses Pemesinan Milling dengan Metode Taguchi Kolaborasi Grey Relational Analysis - Nadila Attin Miftah; Denny Sukma Eka Atmaja; Ayudita Oktafiani (APIC, 2022)
This research focus on multi-objective optimization to minimize surface roughness and maximize material removal rate (MRR) on aluminum alloy 6061 T6. The experiment was designed based on the L9 orthogonal array and was carried out by milling machining process. The input parameters selected from the milling machining conditions are spindle speed, feed rate, and depth of cut. The responses obtained from these experiments are surface roughness and material removal rate. To achieve these two objectives simultaneously, the Taguchi method collaboration with of gray relational analysis can be used. The effect of cutting parameters on surface roughness and MRR can be determined using ANOVA and interaction plots. The optimal parameters to achieve minimum surface roughness and maximum MRR are the combination of a spindle speed of 600 rpm, a feed rate of 50 mm/min, and a depth of cut of 0.7 mm.